PREPARING STUDENTS FOR THE ERA OF ARTIFICIAL INTELLIGENCE: CHALLENGES AND STRATEGIES - Elmiwati; Alim Hardiansyah; Rahmat Shodiqin (CV. ADIBA AISHA AMIRA, 2024)
The era of Artificial Intelligence (AI) has brought significant changes in various aspects of life, including education. The research method in this study used a literature review. The results show that the implementation of this strategy requires a holistic and collaborative approach from all stakeholders in the education ecosystem. The research also underscores the importance of a balance between technical skills and soft skills in preparing students for the AI era. In conclusion, although the challenges are significant, with the right strategies, the education system can evolve to prepare future generations to face and thrive in an era dominated by AI